Herniasi nukleus pulposus lumbal multipel disertai kanal stenosis dengan drop foot syndrome dan atrofi otot unilateral: sebuah laporan kasus - Anak Agung Ngurah Agung Harawikrama Adityawarma; I Nyoman Gede Wahyudana (DiscoverSys Inc., 2021)
Background: Low back pain is a fairly common health problem, with a worldwide prevalence of 1.4-20% and an annual incidence of 0.024-7% per year. One of the causes of lower back pain is a herniated nucleus pulposus. The prevalence of nucleus pulposus herniation in Indonesia is not well documented. One of the complications caused by HNP is drop foot syndrome. Drop Foot Syndrome is the inability to perform flexion dorsum movement of the ankle or big toe. The prevalence of drop foot syndrome is quite rare, with around 8.1% of patients suffering from HN.Case Illustration: A 71-year-old male patient presented with complaints of lower back pain radiating to the left rear thigh since two months ago. The pain was getting worse, and the legs were getting weaker, so that he had to drag his legs. The patient was also often experiencing back pain since five years ago. The patient has a history as a truck driver with the Bali-Java-Sumatra route for 30 years. On physical examination, there ware significant atrophy in the left calf. Motor examination found that the left foot could not lift against the gravity force, and when walking, the big toe touched the floor first. There was no interference with defecation or bowel movements. Lumbar MRI examination was performed with the results of the disc herniation of L1-L2, L2-L3, L4-L5, L5-S1, multiple canal stenosis, and lumbar spondylosis. Discectomy laminectomy and posterior vertebral fusion were performed.Conclusion: HNP is one of the most frequent causes of lower back pain. The lack of knowledge about HNP makes people underestimate this problem, and this is one of the causes of complications in the form of drop foot to muscle atrophy due to the delayed treatment. Latar belakang: Nyeri punggung bawah merupakan permasalahan kesehatan yang cukup umum dengan prevalensi di seluruh dunia sebesar 1,4-20% dan insiden setiap tahunnya 0,024-7%. Salah satu penyebab nyeri punggung bawah adalah herniasi nukleus pulposus. Herniasi nukleus pulposus didefinisikan sebagai rupturnya anulus fibrosus sehingga nukleus pulposus menonjol dan menekan ke arah kanalis spinalis. Salah satu komplikasi yang disebabkan oleh HNP adalah drop foot syndrome. Prevalensi terjadinya drop foot syndrome cukup jarang yakni 8,1% dari pasien yang menderita HNP.Ilustrasi Kasus: Pasien laki-laki berusia 71 tahun datang dengan keluhan nyeri punggung bawah menjalar hingga paha kiri belakang sejak 2 bulan yang lalu. Pasien baru memeriksakan diri ke dokter karena nyeri semakin berat dan kaki semakin lemas sehingga harus menyeret kaki serta mengalami nyeri punggung belakang sejak 5 tahun yang lalu. Pasien memiliki riwayat sebagai pengemudi truk Bali-Jawa-Sumatra selama 30 tahun. Pada pemeriksaan fisik ditemukan atrofi signifikan pada betis kiri, pemeriksaan motorik didapatkan punggung kaki kiri tidak mampu mengangkat melawan gaya gravitasi dan ketika berjalan bagian jempol kaki menyentuh lantai terlebih dahulu serta tidak didapatkan adanya gangguan pada BAB ataupun BAK. Pemeriksaan MRI lumbalis dilakukan dengan hasil herniasi diskus L1-L2, L2-L3, L4-L5, L5-S1, stenosis kanal multipel dan spondilosis lumbalis. Dilakukan laminektomi disektomi dan fusi vertebra posterior.Simpulan: HNP merupakan salah satu penyebab nyeri punggung bawah yang paling sering. HNP menjadi salah satu penyebab terjadinya komplikasi berupa drop foot hingga terjadinya atropi otot karena tidak ditangani lebih awal.